PENGARUH METODE PEMBELAJARAN STUDI KASUS TERHADAP HASIL BELAJAR SISWA DI MTs AL-WASHLIYAH 16 KECAMATAN PERBAUNGAN KABUPATEN SERDANG BEDAGAI - Dhara Khinanti; M. Faisal Husna (STKIP Subang, 2024)
The aim of this research is to determine students' understanding after using the case study learning method and to provide guidance that the use of the case study learning method in Civics subjects can arouse student interest. The design of this research is Classroom Action Research Design (PTK). The subjects of this research are students of class VIIIA2 Al-Washliyah 16, Perbaungan District, Serdang Bedagai Regency, which consists of 33 students with 17 female students and 16 male students. The application of the case study learning method can have a positive influence in improving student learning outcomes in PPKn class VIIIA2 MTs Al-Washliyah 16 Kec. Perbaungan, Serdang Bedagai Regency. The level of student learning completeness in cycle I was 15.16% and increased in cycle II by 69.70%. So the level of completeness of student learning outcomes from cycle I and cycle II has increased by 50%, so the desired target has been achieved for the completeness of student learning outcomes, because at the end of the cycle it has reached the specified target, namely 70%. The application of the case study learning method can increase the results of the percentage of teacher teaching activities from cycle I and cycle II which has increased due to the reform efforts made by the teacher after reflecting on the results of the implementation of cycle I with the average value of the percentage of teacher activities being 43.33% and increasing by 36.67% in cycle II to 80%. The teacher's role in learning influences student learning outcomes, this is because teachers play an important role in managing the learning path from the planning process to the assessment process